Surrogate safety assessment in heterogeneous traffic environment prevailing in developing countries: a systematic literature review - Kumar A.; Mudgal A. (My University, 2025)
Surrogate safety measures (SSMs) are widely used for proactive road safety assessments, reducing reliance on crash data. Despite their potential utility amid escalating road fatalities and lack of good quality crash data in developing countries, SSMs have been predominantly applied in developed countries, where traffic streams are homogeneous, and strict lane discipline is followed. In contrast, traffic in many developing countries (e.g. China and India) is characterized by vehicular heterogeneity and multi-vehicle interactions due to non-lane-based movements. This paper provides a systematic review of 102 peer-reviewed studies in developing countries focusing on vehicular conflicts in traffic streams with heterogeneous vehicle composition and disorderly movement. This review highlights the salient features and challenges associated with SSMs-based safety assessment in developing countries and outlines potential directions for future research. It examines data collection techniques, sample sizes, and the suitability of various conflict indicators for non-lane-based traffic. Additionally, the impact of vehicular heterogeneity on conflict modeling is analyzed. A detailed discussion of conflict segregation methodologies, threshold selection techniques, and modeling frameworks is provided. This review will likely assist in developing more efficient conflict-based safety assessment techniques in heterogeneous traffic, contributing to improved road safety in developing countries. © 2025 Informa UK Limited, trading as Taylor & Francis Group.